2012
DOI: 10.1111/j.1475-097x.2012.01129.x
|View full text |Cite
|
Sign up to set email alerts
|

Validity and interobserver agreement of lower extremity local tissue water measurements in healthy women using tissue dielectric constant

Abstract: The TDC on the foot was significantly higher compared with ankle and lower leg values. Foot measurements should be interpreted cautiously because of questionable interobserver agreement. The interobserver agreement was high on lower leg and ankle measurements. Neither age, BMI, hair removal nor moisturizer use had any significant on effect on the lower leg TDC. TDC values of 35.2 for the ankle and 38.3 for the lower leg are suggested as upper normal reference limits in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…At 300 MHz, the contribution of conductivity to the overall value of the permittivity is small and the TDC is mainly determined by water molecules (free and bound). Further details including validation and repeatability data are described in the literature (Nuutinen et al ., ; Jensen et al ., ; Mayrovitz, ). Each probe is calibrated against various ethanol–water mixture concentrations each of known dielectric constant values (Mayrovitz, ).…”
Section: Methodsmentioning
confidence: 99%
“…At 300 MHz, the contribution of conductivity to the overall value of the permittivity is small and the TDC is mainly determined by water molecules (free and bound). Further details including validation and repeatability data are described in the literature (Nuutinen et al ., ; Jensen et al ., ; Mayrovitz, ). Each probe is calibrated against various ethanol–water mixture concentrations each of known dielectric constant values (Mayrovitz, ).…”
Section: Methodsmentioning
confidence: 99%
“…Part of the signal is absorbed, mainly by tissue water, and part is reflected back to permit the calculation of the complex reflection coefficient (Lahtinen et al, 1997;Lan et al, 2007) from which the dielectric constant is determined (Alanen et al, 1998b). Further details including prior uses for skin assessments, validation and repeatability data are described in the literature (Nuutinen et al, 2004;Jensen et al, 2012;Mayrovitz et al, 2013). At 300 MHz, conductivity contributes little to the overall permittivity value and TDC is mainly determined by free and bound water molecules.…”
Section: Measurementsmentioning
confidence: 99%
“…The TDC values of the foot were significantly different from the ankle and lower‐leg values. Previous studies have demonstrated that TDC values vary between different anatomical regions, as the TDC value is influenced by different layers of tissue at different measurement sites . Subcutis and fat are known to have relatively low water content, while dermis, connective tissue (including tendons), blood vessels, muscle, bone and nerves have a relatively high water content .…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Clinical studies on healthy subjects have demonstrated good intra-and interobserver agreement. 11,12 It has been demonstrated that TDC values are influenced by anatomical measurement site, 12,13 measurement depth, 13,14 and subject sex, 15 body mass index (BMI) and age. 14 TDC measurements have been applied successfully in clinical studies evaluating oedema of varying aetiologies, and oedema changes in skin irritation, 16 skin irradiation, 17,18 haemodialysis, 19 postcardiac surgery, 20 breast-cancer-related arm lymphoedema 11,21,22 and lymphoedema of the lower extremities.…”
Section: What Does This Study Add?mentioning
confidence: 99%
See 1 more Smart Citation